EFFECTIVENESS OF COMMUNICATION IN AN ORGANIZATION IN THE CRISIS PERIOD OF COVID-19 - Tuty Mutiah; Fitriyanto Fitriyanto; Juniarti Eka Sapitri; Ilham Albar; Yusni Mirat La Ode (FISIP UPNVJ, 2020)
Abstract: The rapid spread of Covid-19 disease made the whole country move to deal with this problem. Indonesia is also not free from this problem; the spread of the corona virus has reached the country. In order to combine the effectiveness of communication in an organization to achieve conditions consisting of various thoughtful processes and anticipatory steps in a crisis period of covid-19. The need for communication in today's business competition is constantly changing. Advances in information technology and changes in managing organizations have changed the way many organizations in delivering the information. Information technology is a tool to communicate with many different groups of people. Since then the communication process must be managed effectively not all managers and individuals in an organization have good communication skills and there is a clear need for training to ensure that they could choose the most appropriate communication method to convey the message clearly understood by the recipient and on the side otherwise, the recipient must be able to provide feedback.Keywords: Message, communication method, communication effectiveness, Covid-19